Anthropometric Measurement of Maximum Tibia Length in South Indian Population - Prasanna Veera Kumar Attada; Gandrakota Ravindranadh; Kolla Deena Usha Kumari (Negah Institute for Scientific Communication, 2018)
Introduction: The human stature forms part of his or her biological profile. It becomes more important during personal identification in case of mass disasters and in search of missing persons. We measured various parameters of the dried tibia, then by applying linear regression we formulated maximum tibia length which can be conveniently used for arriving at human stature. Methods: The obtained data were analyzed by descriptive statistics methods and expressed as mean (SD). The Pearson correlation coefficient (r) was used to express the relationship between the Maximum Tibia Length (MTL) and other parameters of tibia. The linear regression analysis was performed and the regression equation was arrived for the prediction of MTL. Results: The mean (SD) score with respective Standard Errors of Estimate (SEE) for both right and left tibia were found, irrespective of the bone side. The mean maximum length of the right and left tibia were 37.50(3.03) cm and 37.05(3.12) cm, respectively. The mean maximum length of tibia, irrespective of side was calculated as 37.20(3.04) cm. The correlation coefficient between MTL and other tibial parameters were derived.  Conclusion: Estimation of maximum tibia length with regards to its measured anthropometric parameters in south Indian population can help in evaluating human stature even when a segment of tibia is available for measurement, which is population-specific.